Applications of the Kharkov potential in the theory of nuclear forces and nuclear reactions - Arslanaliev, A.; Kamada, H.; Shebeko, A.; Stepanova, M.; Witala, H.; Yakovlev, S. (Вопросы атомной науки и техники, 2018)
The Kharkov potential is a recent field theoretical model of nucleon-nucleon (NN) interaction that has been built up in the framework of the instant form of relativistic dynamics starting with the total Hamiltonian of interacting meson and nucleon fields and using the method of unitary clothing transformations (UCTs). The latter connect the representation of “bare” particles (BPR) and the representation of “clothed” particles (CPR), i.e., the particles with physical properties. Unlike many available NN potentials each of which is the kernel of the corresponding nonrelativistic Lippmann-Schwinger (LS) equation this potential being dependent in momentum space on the Feynman-like propagators and covariant cutoff factors at the meson-nucleon vertices is the kernel of relativistic integral equations for the NN bound and scattering states. We show our calculations with the Bonn and Kharkov potentials for such quantities as the phase shifts in the neutron-proton scattering up to the pion production threshold, the binding energies of deuteron and triton, the nucleon momentum distributions in these nuclei and some Nd elastic scattering observables. Special attention is paid to finding from the contemporary n-p phase shift analysis some optimum values of the adjustable parameters included.